Status of fertilizer and seed subsidy in Nepal: review and recommendation - Bista, Diwas Raj; Dhungel, Sujan; Adhikari, Santosh (Journal of Agriculture and Environment, 2018)
The study focuses on the review of existing programs and policies regarding input subsidy in Nepal especially in seeds and fertilizers. The study aims to review timeline in subsidy programs, budget details and progress based on the gleaning of the secondary information available in the Ministry of Agricultural Development. The assured budget allocation for chemical fertilizers subsidy has led to increment in consumption over the years. Nepal spent 52.29 billion Nepali Rupees in importing chemical fertilizers and 23.19 billion in subsidy in last seven years. Nepal Government has also been promoting organic fertilizers however, the subsidy allocated to this program has not been able to take the pace. Seed subsidy program has been found to be impressive; however, it is confined to wheat and paddy only. The subsidy program is targeted mainly to the small and marginal farmers. The seed subsidy program should be expanded to pulses and oilseed crops as well. The organic fertilizers should be promoted to maintain long-term soil health. Inputs subsidy policy and programs should cover all farmer categories.